Vedení a řízení spolupracovníků ve stavebním podniku - Kráčmarová, Martina (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Abstrakt Předmětem bakalářské práce je „Vedení a řízení spolupracovníků ve stavebním podniku“. V teoretické části je stručně popsán pojem managementu, managementu ve stavebnictví, vedení a řízení pracovníků, zejména z hlediska jejich komunikace, naslouchání, synergie, s tímto spojené týmové práce Zabývala jsem se zde i charakterem manažera, jako důležitou součástí řídící práce, která se promítá do všech jeho činností. V empirické části je, vedle pracovních hypotéz, využita forma dotazníku k dané problematice celého empirického šetření a jeho vyhodnocení. V závěrech a doporučeních najdeme trendy a zkušenosti, které z výzkumu vyplynuly, jako inspiraci pro praxi stavebního podniku.

Abstract The subject of this Bachelor Thesis is "Leadership and staff management in the construction business." In the theoretical part there is briefly described the concept of management, construction management, as well as employee management and leadership, particularly in terms of communication, listening and teamwork synergies associated with that. I was looking into a personal nature of a manager, which is an important aspect influencing the management work, reflected in all managers’ activities. In the empirical part, besides working hypotheses, there is a questionnaire utilized to form the whole issue of the empirical investigation and its evaluation. In the conclusion and in the recommendations we can find trends and experience that result from the research, as an inspiration for the practice of a construction enterprise.
Leadership and management of employees in the construction company
Keywords: Klíčová slova; Vedení; řízení; komunikace; naslouchání; empatie; synergie; týmové vztahy; konflikt.; Key words; Leadership; management; communication; listening; empathy; synergy; team relationships; conflict.